“Toronto Has No History!”: Indigeneity, Settler Colonialism, and Historical Memory in Canada’s Largest City - Freeman, Victoria (Urban History Review / Revue d'histoire urbaine, 2010)
In 1884, during a week-long commemoration of the fiftieth anniversary of Toronto’s incorporation in 1834, tens of thousands celebrated Toronto’s history and its relation to British colonialism and imperialism. The author’s analysis of the historical tableaux in the first day’s parade and speeches by Daniel Wilson, president of University College, and Chief Samson Green of the Tyendinaga Mohawks reveals divergent approaches to commemoration as “politics by other means”: on one hand, the erasure of the area’s Indigenous past and the celebration of its European future, on the other, an idealized view of the past of Indigenous–settler partnership that ignores the role of local settlers in the dispossession of the Mississaugas. The 1884 commemoration marks the transition from the founding of the settlement in 1793 to its incorporation in 1834 as the city’s “founding moment” and marker of the assumed “indigeneity” of settler-immigrants. The deed acquired from the Mississaugas in the Toronto Purchase of 1787 is deemed irrelevant, while the 1834 Act of Incorporation becomes the symbolic deed to Toronto’s modernity.